2017
DOI: 10.3390/app7121324
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth Widening of Piezoelectric Cantilever Beam Arrays by Mass-Tip Tuning for Low-Frequency Vibration Energy Harvesting

Abstract: Featured Application: The results of the present work can be used to develop vibration energy harvesters supplying wireless sensor nodes. This is feasible since the order of magnitude of harvested electrical power is 1 mW.Abstract: Wireless sensor networks usually rely on internal permanent or rechargeable batteries as a power supply, causing high maintenance efforts. An alternative solution is to supply the entire system by harvesting the ambient energy, for example, by transducing ambient vibrations into ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Moreover, the three bimorphs system has a larger output power, and by adding an additional bimorph (the middle one), the width of the “power pit” is reduced. Similar results were published in [26,37]. …”
Section: Parametric Investigationsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the three bimorphs system has a larger output power, and by adding an additional bimorph (the middle one), the width of the “power pit” is reduced. Similar results were published in [26,37]. …”
Section: Parametric Investigationsupporting
confidence: 92%
“…A preferred end mass ratio should be 10–20, depending on system geometry and spring rate. The same conclusion can be found in [26,37]. Note that a complete disappearance of the power pit can be achieved only for the case of two very close natural frequencies, yielding a narrow bandwidth, and therefore not applicable.…”
Section: Conclusion and Summarysupporting
confidence: 80%
See 1 more Smart Citation
“…Several papers [2][3][4][5] present the multiple cantilever beam arrays. It increases bandwidth and electric power for scavenge vibration energy ambient.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is indicated that the nonlinear behavior can not only offer new capabilities to capture energy available from more complex excitations but also have the advantage of broadening the frequency range of vibrations energy harvesting. 2,3 By the super-harmonic vibration behavior, a nonlinear resonator is designed and fabricated for ultra-wide-bandwidth energy harvesting applications, 4 the nonlinear resonances can activate large-amplitude motions at fraction integers of the fundamental frequency of the system, 5 a mathematic model for the nonlinear energy harvester may be simplified as the form of a Duffing oscillator 6 and a new method for the dynamical features of stochastic nonlinear oscillators is proposed, 7 and the performances of nonlinear energy harvesters are researched by exploiting benefits of a periodically forced double-well oscillator. 8 However, it has been thought that the smart structures have other nonlinearity, for example, hysteresis phenomenon.…”
Section: Introductionmentioning
confidence: 99%